Effects of skin care education for care staff at elderly care facilities on skin conditions of the residents. Issue 4 (7th January 2020) - Tsunemi, Yuichiro; Nakagami, Gojiro; Takehara, Kimie; Tamai, Nao; Kitamura, Aya; Mugita, Yuko; Oe, Makoto; Kishida, Momoyo; Sanada, Hiromi
Abstract: Asteatosis is common in elderly people due to a decrease in the moisture content of the epidermal stratum corneum through a loss of skin barrier function caused by aging. Because itching often accompanies asteatosis, this condition may cause a decrease in quality of life. Care staff in elderly care facilities have many opportunities to provide care for residents. In this study, we examined how educational training on skin care changed the thoughts and actions of care staff in these facilities and how these changes impacted the skin conditions of residents. The subjects for the training were all care staff in facilities because these staff work most closely with facility residents. We performed skin care training for the subjects and investigated changes in the skin conditions of the residents before and after the training. The training promoted the understanding of skin care among the care staff and improved the skin symptoms of residents with asteatosis. However, there were no changes in the severity of itchiness based on a verbal rating scale and in interviews of residents. This study showed that skin care training for the care staff in facilities is effective to improve skin conditions of residents. In addition, it was suggested that a full grasp of the residents' skin symptoms based upon an interview on itching alone was difficult, and thus there is a need to observe skin conditions directly.